2022
DOI: 10.3329/bjms.v21i4.60255
|View full text |Cite
|
Sign up to set email alerts
|

“They shouted at me to discontinue exclusive breastfeeding”: narratives of mothers in Limpopo Province of South Africa as they grabble with exclusive breastfeeding

Abstract: Objective: Exclusive breastfeeding for the first six months of an infant’s life is an internationally recognised practice that promotes maternal and child health. Mothers and their infants reap health and socioeconomic benefits from exclusive breastfeeding. Even with these benefits, exclusive breastfeeding is still a challenge for some mothers to practice. Many studies revealed numerous challenges and enablers, and proposed comprehensive solutions, but implementation of exclusive breastfeeding for six months r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Research conducted in the Limpopo Province, South Africa, indicated that caregivers gave solid foods to infants before they were 6 months old. It was also discovered that exclusive breastfeeding was lower than the World Health Organisation (WHO) standards [ 26 , 27 ]. In many countries, only a few children obtain complementary foods that are safe and nutritionally adequate; just a minority of infants, aged between 6 and 23 months, satisfy the WHO standards for age-appropriate dietary diversity and feeding frequency [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in the Limpopo Province, South Africa, indicated that caregivers gave solid foods to infants before they were 6 months old. It was also discovered that exclusive breastfeeding was lower than the World Health Organisation (WHO) standards [ 26 , 27 ]. In many countries, only a few children obtain complementary foods that are safe and nutritionally adequate; just a minority of infants, aged between 6 and 23 months, satisfy the WHO standards for age-appropriate dietary diversity and feeding frequency [ 28 ].…”
Section: Introductionmentioning
confidence: 99%